Strategi Dalam Upaya Mengembangkan Ruang Kelas Yang Berkarakter - M Adi Pratama Putra; Alfinda Adelia Dirli (Pusat Riset dan Inovasi Nasional, 2023)
Character education gets a lot of attention nowadays. Today, when there are many occurrences of deviant behavior, character education is needed to minimize the implementation of deviant acts. Character education is applied to instill character points in everyone, which leads to changes in behavior from bad to good. To optimally instill character values ​​in each person, character education is applied. must start earlier. Elementary school education plays an important role in character education in this regard. The success of character education is influenced by several factors, one of which is a conducive atmosphere in the classroom. Through a class atmosphere with character, students can create ways to always behave well. Creating a personalized learning space requires the role of the teacher. Because people spend a lot of time at school interacting with students, teachers certainly have many opportunities to instill student character points, this time by creating character learning spaces. Some things that teachers can do to build character are: 1) imitate character, 2) teach manners, teach character academics, train character-based discipline, 5) teach manners, prevention. violations of peers and the priority of goodness, 6) directing children to be responsible for forming their own character.